Automation and future of garment sector jobs: A case study of India - Pankaj Vashisht; Nisha Rani (Indian Council for Research on International Economic Relations (ICRIER), 2019)
Robotics has been redefining the production process across manufacturing industries, raising serious concern about the future of jobs and the garment sector is not isolated. The recent innovations such as "Sewbot" along with other Computer Numeric Control machines have increased the risk of technology-induced displacement of labour in the garment sector. This paper examines the technical and economic feasibility of automation in the Indian garment sector and its likely impact on jobs. Based on secondary data analysis and key informant interviews, the paper argues that though technically robotics can displace 80 per cent labour employed in the Indian garment sector, the actual displacement is going to be much lower as, owing to the economic feasibility, automation is going to be restricted to a few garment production processes only. Paper further argues that despite the automation of the certain production processes, Indian garment sector will register healthy employment growth as expansion in domestic garment demand will be more than sufficient to offset the labour-saving effect of technology.
Keywords: O33; L67; J21; 330; Robotics; Garment; Technology